Use of Wrist or Ankle as Substitute Sites for Placement of Pulse Oximeter in Neonatal Intensive Care - Dahal, Sonia; Rimal, Hemsagar; Pyakurel, Kumud; Adhikari, Deep Raj (Birat Journal of Health Sciences, 2021)
Introduction: Pulse oximetry is widely used in Neonatal intensive care setting. Both wrist and ankle are widely used as substitute sites for probe placement in place of more commonly used sites such as palm and sole. However, little is known about the accuracy and response time of pulse oximetry when the probe is placed at wrist or ankle of neonates. Objectives: The primary objective of this study was to compare the values of SpO2 reading at wrist with palm and ankle with sole in terms of correlation and accuracy. The secondary objective was to compare the response time to get a valid SpO2 reading at wrist with palm and ankle with sole. Methodology: This was a prospective observational study conducted at Neonatal intensive care unit of Biratnagar Hospital from October 2020 to January 2021. After approval from institutional review committee, a total of 152 consecutive neonates admitted in NICU of either gender both term and preterm were enrolled for the study. Recording of SpO2, heart rate and response time was done by two pulse oximeters simultaneously. The SpO2 measurements at right palm and right wrist were recorded at 0, 30 seconds and 1 minute then simultaneous recording was done for the left palm and left wrist, right sole and ankle and left sole and ankle. Response time was also recorded for each of the readings. Results: The results of our study show good correlation using regression analysis and good agreement using Bland- Altman plots between the values of SpO2 reading of paired measurements. The response times of the paired measurements were not significantly different. There was good correlation between the SpO2 of paired measurements. The correlation for right palm and wrist was 0.927 (P-value = 0.01) and that of left palm and wrist was 0.85 (P-value = 0.01). Similarly the correlation between right sole and ankle and left sole and ankle were 0.937 (P-value = 0.01) and 0.875 (Pvalue = 0.01) respectively. The bias (average difference) and precision (standard deviation of differences) were calculated. The bias and precision of the right palm and wrist, left palm and wrist, right ankle and sole; and left ankle and sole were (-0.00289, 0.76105), (-0.17982, 0.95049), (-0.03509, 0.786342) and (-0.14474, 0.859241) respectively. Conclusion: Wrist and ankle can be used as substitute sites for pulse oximter placement in neonatal intensive care setting.